THE IMPORTANCE OF THE INTERACTIVE METHODS IN TEACHING ENGLISH IN SCHOOL EDUCATION (Eureka Journal of Language, Culture & Social Change, 2026)
Modern actions in the teaching process and the modernization of current teaching and learning approaches are necessary in today's educational space. The educational system has been modified for this reason, and its primary goal is to assist pupils in gaining as much knowledge as possible. According to research, interactive instruction maximizes student engagement in the classroom. The student remains in the role of the listener when using interactive teaching techniques, but they actively participate. Students learn new material with ease and retain it for a long time. This article highlights the value of contemporary interactive teaching techniques and emphasizes how well they stimulate students' critical thinking, problem-solving, independent study, and teamwork abilities.
Keywords: Modernization of teaching, educational system, interactive instruction, student engagement, interactive teaching techniques, critical thinking, problem-solving, independent study, teamwork abilities.